N3‐Sensitized TiO2/Nb2O5: A Novel Bilayer Structure for Dye‐Sensitized Solar‐Cell Application. Issue 18 (25th June 2018) - Beedri, Niyamat I.; Baviskar, Prashant K.; Bhalekar, Vikram P.; Jagtap, Chaitali V.; , Inamuddin; Asiri, Abdullah M.; Jadkar, Sandesh R.; Pathan, Habib M.
Abstract : A simple and cost‐effective chemical precipitation method for the synthesis of Nb2 O5 nanoparticles is reported. The as‐synthesized powder is amorphous and after annealing at 500 °C the crystalline phase is observed, which is then used for the preparation of photoelectrode material sensitized with N3 dye toward dye sensitized solar‐cell application. The effect of Nb2 O5 layer over TiO2 by making a bilayer structure for dye‐sensitized solar‐cell application is studied. The device performance is studied using the current density–voltage ( J–V ) curve as well as by external quantum efficiency measurement (EQE). Furthermore, the behavior of electron in the device is studied by electrochemical impedance spectroscopy (EIS) measurement. It is observed that the amount of dye loading increases with optical reflection for the bilayer structure, which leads to the improvement in J SC along with EQE. The maximum power conversion efficiency obtained for the bilayer structure is 5.26%. Abstract : In this research, Nb2 O5 blocking layer is coated by using a doctor blade technique over TiO2 . There is a high electron recombination resistance for device fabricated with TiO2 /Nb2 O5 photoanode compared to TiO2 ‐ and Nb2 O5 ‐based devices. The main factorto improve the efficiency is the formation of the Nb2 O5 blocking layer on TiO2 .